PICTURES IN READING COMPREHENSION - Abdul Rabbi Arrasul (BABASAL English Education Journal, 2020)
The objective this research is to determine whether the use of pictures can improve students of class VII at SMPN 2 Bunta. This research used a quasi-experimental study that required a posttest for both groups. The population of this research was the students of class VII at SMPN 2 Bunta. The sample of this research  were class VIIA as an experimental class consisting of 22 students and class VIIB as a control class consisting of 20 students. In collecting data, the researcher used test. The test consisted of pretest and posttest. Data were analyzed statistically. After being analyzed, it was found that the result of the t-count was 2,45. With 40 degree of freedom, and a the significance level of 0,05, the t-table was 2,021.Therefore, the result of t-count is higher than t-table. The results showed that there was an increase, although not significant towards the use of pictures in improving students’ reading comprehension of class VII at SMPN 2 Bunta. It means that the hypothesis of this research is accepted.